Terrestrial invasions on sub-Antarctic Marion and Prince Edward Islands - Greve, Michelle; Mathakutha, Rabia; Steyn, Christien; Chown, Steven L. (African Biodiversity & Conservation, 2017)
Background: The sub-Antarctic Prince Edward Islands (PEIs), South Africa’s southernmost territories have high conservation value. Despite their isolation, several alien species have established and become invasive on the PEIs.Objectives: Here we review the invasion ecology of the PEIs.Methods: We summarise what is known about the introduction of alien species, what influences their ability to establish and spread, and review their impacts.Results: Approximately 48 alien species are currently established on the PEIs, of which 26 are known to be invasive. Introduction pathways for the PEIs are fairly well understood – species have mainly been introduced with ship cargo and building material. Less is known about establishment, spread and impact of aliens. It has been estimated that less than 5% of the PEIs is covered by invasive plants, but invasive plants have attained circuminsular distributions on both PEIs. Studies on impact have primarily focussed on the effects of vertebrate invaders, of which the house mouse, which is restricted to Marion Island, probably has the greatest impact on the biodiversity of the islands. Because of the risk of alien introductions, strict biosecurity regulations govern activities at the PEIs. These are particularly aimed at stemming the introduction of alien species, and are likely to have reduced the rates of new introductions. In addition, some effort is currently being made to eradicate selected range-restricted species.  However, only one species that had established and spread on the PEIs, the cat, has beensuccessfully eradicated from the islands.Conclusion: Given the ongoing threat of introductions, and the impacts of invaders, it is essential that future invasions to the PEIs are minimised, that the islands’ management policies deal with all stages of the invasion process and that a better understanding of the risks andimpacts of invasions is obtained.